LIQUID CONSUMPTION, WORK LOADS AND HEAT STRESS WITH WORK FATIQUE - Diki Bima Prasetio; Juni Arum Sari (Poltekkes Kemenkes Semarang, 2020)
Work fatigue is a form of body protection mechanism to avoid further damage and recovery after rest. Tire patch workers who work on the roadside are very vulnerable to work fatigue. This study aims to determine the relationship between fluid consumption, workload and heat stress with work fatigue. This type of research is observational with cross sectional approach. The sample of this research is 44 tire patch workers on the edge of Jalan Mugas Raya Semarang. Data analysis was performed with the Pearson Chi Square test. The results showed that workers who experienced high category of work fatigue by 50% and obtained a relationship between fluid consumption (p = 0.043), workload (p = 0.004), heat pressure (p = 0.033) with work fatigue. The conclusion is that the majority of workers who use tire patches on the roadside experience work fatigue, so they need to get health guidance.